AN ANALYSIS OF THE ENGLISH TEACHING AND LEARNING PROCESS IN ACCORDANCE WITH THE 2013 ENGLISH CURRICULUM AT SMA NEGERI 3 JAMBI - Akhmad Habibi (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2016)
AN ANALYSIS OF THE ENGLISH TEACHING AND LEARNING PROCESS IN ACCORDANCE WITH THE 2013 ENGLISH CURRICULUM AT SMA NEGERI 3 JAMBI Akhmad Habibi English Education Study Program, Jambi University, Jambi, Indonesia tjohor@ymail.com Abstract: This study was aimed at analysing the implementation of teaching and learning process as one of the standard of process parts in the 2013 Curriculum. This was a qualitative study with a case study approach conducted at SMA Negeri 3 Jambi. Three English teachers and 237 students of grade XI were involved as the participants. The data were collected through interview with the teachers, observation, students’ questionnaire, and document review. To assess the trustworthiness of this study, the researcher did triangulation, member checking and reflexivity.The findings covered the analysis of the implementation of teaching and learning process which included two-essentially scripted aspects: classroom management and teaching and learning process. The classroom management was grouped into three sub-themes: teaching performance, classroom attitude, and time management. Teaching and learning process implementation covered three activities: introductory, core, and closing activities. Based on the findings, suggestions such as to limit the number of the students, to provide cutting-edge technology devices, and to hold trainings for teachers, were proposed for teachers of English, schools, and educational authorities, respectively. Key words: analysis, classroom management, the English teaching and learning process, 2013 English Curriculum